Case Report: Dislocation Into Vitreous Cavity and Removal of a Posterior Chamber Phakic Intraocular Lens - He, Jingliang; Zhang, Li; Zheng, Fang; Fang, Xiaoyun (Frontiers in Medicine, 2022)
Purpose: To report a rare case of delayed dislocation of a novel posterior chamber phakic intraocular lens into the vitreous cavity, which was successfully treated by a reformed technique. Case Presentation A 29-year-old female received Ejinn phakic refractory lens (EPRL) implantation to correct her high myopia. Spontaneous dislocation into the vitreous cavity occurred 26-months post-operatively without traumatic history. Pars plana vitrectomy combined with cutting the EPRL into two equal pieces was performed to remove the dislocated EPRL. Conclusion Dislocation into the vitreous cavity of EPRL can be successfully and easily removed by our reformed technique. Concerns about zonules-related complications pre-operatively, intraoperatively, and post-operatively must be raised in the practice of EPRL implantation.